Blockade of Serotonin 5-HT2A Receptors Suppresses Behavioral Sensitization and Naloxone-Precipitated Withdrawal Symptoms in Morphine-Treated Mice - Pang, Gang; Wu, Xian; Tao, Xinrong; Mao, Ruoying; Liu, Xueke; Zhang, Yong-Mei; Li, Guangwu; Stackman, Robert W.; Dong, Liuyi; Zhang, Gongliang (Frontiers in Pharmacology, 2016)
The increasing prescription of opioids is fueling an epidemic of addiction and overdose deaths. Morphine is a highly addictive drug characterized by a high rate of relapse – even after long periods of abstinence. Serotonin (5-HT) neurotransmission participates in the development of morphine dependence, as well as the expression of morphine withdrawal. In this study, we examined the effect of blockade of 5-HT2A receptors (5-HT2ARs) on morphine-induced behavioral sensitization and withdrawal in male mice. 5-HT2AR antagonist MDL 11,939 (0.5 mg/kg, i.p.) suppressed acute morphine (5.0 mg/kg, s.c.)-induced increase in locomotor activity. Mice received morphine (10 mg/kg, s.c.) twice a day for 3 days and then drug treatment was suspended for 5 days. On day 9, a challenge dose of morphine (10 mg/kg) was administered to induce the expression of behavioral sensitization. MDL 11,939 (0.5 mg/kg, i.p.) pretreatment suppressed the expression of morphine-induced behavioral sensitization. Another cohort of mice received increasing doses of morphine over a 7-day period to induce morphine-dependence. MDL 11,939 (0.5 mg/kg, i.p.) prevented naloxone-precipitated withdrawal in morphine-dependent mice on day 7. Moreover, chronic morphine treatment was associated with an increase in 5-HT2AR expression and a decrease in phosphorylation of extracellular signal-regulated kinases in the prefrontal cortex. Together, these findings provide the first evidence to support the view that the 5-HT2AR modulates opioid dependence and blockade of 5-HT2AR may be a novel strategy for the treatment of morphine abuse and dependence.